Loss of Eed leads to lineage instability and increased CD8 expression of mouse CD4+ T cells upon TGFβ signaling. (February 2018) - Naito, Taku; Muroi, Sawako; Taniuchi, Ichiro; Kondo, Motonari
Highlights: Eed loss enhances CD8α expression of CD4 + T cell in TGFβ-driven Treg-polarizing conditions in vitro . CD8α genetics in TGFβ-stimulated Δ Eed CD4 + cells is similar to CD4 + CD8αα + IELs. Eed blocks DP-IEL-like phenotype by decreased loci accessibility and Smad3 binding. Smad3 and T-bet-Runx3 axis cooperation is critical for a DP-IEL-like phenotype. Abstract: Tri-methylation of lysine 27 on histone H3 (H3K27me3) is a repressive epigenetic modification catalyzed by polycomb repressive complex 2 (PRC2) that is required for proper cell fate determination as well as cellular function. Numerous studies have been performed to elucidate the role of PRC2 in T-cell differentiation and function; however, its role in the regulation of T-helper (Th) subset differentiation and identity has not been fully explored. Here, we report that Eed, an essential subunit of PRC2, is crucial to maintain the identity of CD4 + T cells under TGFβ-induced regulatory T cell (Treg)-polarizing conditions. Mouse CD4 + T cells lacking Eed exhibited unstable CD4 expression upon TCR stimulation in vitro . Helper lineage instability was further augmented by Treg-polarizing conditions, leading to the immense up-regulation of CD8α as well as other molecules, resembling CD4 + CD8αα + intraepithelial lymphocyte (DP-IEL) differentiation. Genetic studies suggested that the altered balance between transcription factors T-bet, Runx3, and Th-POK underlies the induction of the DP-IEL-like phenotype in Eed -deficient CD4 + cells. Furthermore, comparison to Th1- and Th17-polarizing conditions indicated that cooperation between Smad3 and the T-bet-Runx3 axis facilitated by the loss of H3K27me3 is crucial for phenotype induction. Collectively, our results provide insight into the molecular mechanism that maintains and regulates the proper cellular response upon TGFβ signaling in CD4 + T cells.